Health behavioral responses to parental myocardial infarction and impact on own risk of disease in the general population - Skouenborg, Christian; Jørgensen, Martin Lucas; Nielsen, Torben Heien; Benn, Marianne (Frontiers in Public Health, 2023)
A family history of coronary heart disease increases one's own risk of experiencing cardiovascular disease and death. An implication of the hereditary nature of the disease is that individuals are provided information about their own risk when a parent is affected, potentially leading them to engage in behaviours that reduce their own risk. In this study we assessed how 10-year risk of a cardiovascular event, measured by SCORE, changes for the offspring in response to a parent experiencing a myocardial infarction.We analysed 19,995 individuals from the general population, the Copenhagen City Heart Study of whom 2,071 had a parent, who suffered from a myocardial infarction during four decades of observation using fixed-effects regressions.Following a parental myocardial infarction, individuals reduced their 10-year risk with 0.16 percentage points constituting a 7.1% reduction of baseline risk. Male participants had the largest change in risk SCORE following an event of the mother, with a 12.4% reduction from baseline risk.Degree of response contingent on own level of risk was found to be largest for individuals with a 10-year risk between 5-10%, who also show a reduction in systolic blood pressure following paternal myocardial infarction. Parental myocardial infarction was associated with an increased smoking rate for individuals with a baseline risk above 10%, and points towards reductions for individuals with lower baseline risk.Following a parental event, individuals reduced their 10-year risk with largest reductions in own risk observed in males and individuals experiencing a maternal event. Response was largest for individuals with a 10-year risk for myocardial infarction between 5-10%.